Cayc group at the bank of Ireland Dublin : Jacques Bedel - Luis Benedit - Jorge Glusberg - Jorge González Mir - Victor Grippo - Leopoldo Maler - vicente Marotta - Alfredo Portillos - Clorindo Testa. - bank of Ireland, Dublin; Centro de Arte y Comunicacion, Buenos Aires (Buenos Aires : Centro de Arte y Comunicación, 1980)
Bedel, Jacques ; Benedit, Luis ; Glusberg, Jorge ; Gonzalez Mir, Jorge ; Grippo, Victor ; Maler, Leopoldo ; Marotta, Vicente ; Portillos, Alfredo ; Testa, Clorindo
Cayc group at the bank of Ireland, Dublin in association with Rosc '80 the poetry of vision, september 1980
boek